2021
DOI: 10.1088/1572-9494/abfcb1
|View full text |Cite
|
Sign up to set email alerts
|

Optical solitons for the decoupled nonlinear Schrödinger equation using Jacobi elliptic approach

Abstract: Most of the important aspects of soliton propagation through optical fibers for transcontinental and transoceanic long distances can best be described using the nonlinear Schrödinger equation. Optical solitons are electromagnetic waves that span in nonlinear dispersive media and permit the stress and intensity to stay unaltered as a result of the delicate balance between dispersion and nonlinearity effects. However, this study exploited the Jacobi elliptic method and obtained different soliton solutions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the field of mathematics, the study of nonlinear equations with variable coefficients has also led to the further development of integrable systems. The similar transformation technique, Wronskian technique, Jacobi elliptic approach, and direct algebraic method can solve the nonlinear Schrodinger equation with variable coefficients [7][8][9][10]. By using the similar transformation technique, we can solve the optically smooth position solution of the nonlinear Schrodinger equation with variable coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of mathematics, the study of nonlinear equations with variable coefficients has also led to the further development of integrable systems. The similar transformation technique, Wronskian technique, Jacobi elliptic approach, and direct algebraic method can solve the nonlinear Schrodinger equation with variable coefficients [7][8][9][10]. By using the similar transformation technique, we can solve the optically smooth position solution of the nonlinear Schrodinger equation with variable coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…The optical soliton theory is used in many applications of telecommunications, ocean engineering, and other areas of science [6][7][8].The nonlinear Schrödinger equation and its different modified forms have been explored by many researchers to understand the light propagation through optical media. Some recent studies have reported useful results on the optical soliton theory using the ansatz method [9], Jacobi elliptic method [10], extended tanh-coth expansion technique [11], and Kudryashov expansion technique [12].…”
Section: Introductionmentioning
confidence: 99%